The Influence Of Profitability, Investment Opportunity Set And Disclosure Of Islamic Social Reporting On Firm Value (Empirical Study On Companies Registered In The Jakarta Islamic Index 2019-2022) - Ahmad Mufid Hanafi; Nursiam Nursiam (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine and analyze the effect of profitability, investment opportunity set and Islamic social reporting on firm value. company values. The population of this study are publicly listed companies whose shares are listed on the Jakarta Islamic Index during the 2019-2022 period. whose shares are listed on the Jakarta Islamic Index during the 2019-2022 period. The technique sampling technique in this study using purposive sampling method, with the results of 23 companies that meet the predetermined criteria with a total. sample of 92 samples. determined with a total sample size of 92 samples. This research uses multiple regression data analysis methods with the help of the SPSS version 26 program. The data used in this study are secondary data obtained from the company's published financial statements from the company's website. obtained from financial reports published by the company from the website www.idx.co.id. The results of this study indicate that the investment opportunity set variables and Islamic social reporting have an effect on firm value. company values. While profitability has no effect on firm value